BER Analysis of 2x2 Spatial Multiplexing under AWGN and Rayleigh Channels for Different Modulations (Global Journals of Research in Engineering, 2013)
Spatial multiplexing SM which employs multiple antennas at the transmitter and the receiver end has recently been shown to be one of the most promising technologies in future wireless communication systems In this paper analysis of high level modulations i e M-PSK for different values of M is done Here AWGN and Rayleigh channels have been used for analysis purpose and their effect on BER for high data rates have been presented The signal detection technique used at receiver end is Zero-Forcing Equalization ZF and Minimum Mean Square estimator MMSE linear detection techniques
Keywords: spatial multiplexing (SM); multiple-input multiple-output (MIMO); bit error rate (BER); zero forcing (ZF); minimum mean square estimator (MMSE)